Japan’s experience in organizing and promoting separate accumulation of municipal solid waste (MSW) - А. N. Larionova (Японские исследования)
The article considers the Japanese system of municipal solid waste management as well as work with the population in the field of environmental education. The roles and responsibilities of the parties in the management of municipal solid waste are analyzed. In Japan, unlike other countries, the state is deeply involved in the process. Sorting and disposal of waste occur at the municipal level due to the historical characteristics of the Japanese society. Extended producer responsibility requires their participation from product development to disposal, and consumers are required to cooperate with them and local authorities by properly disposing solid waste. The regulatory framework in the field of MSW management is built around the Basic Act on Establishing a Sound Material-Cycle Society and the Law for Promotion of Effective Utilization of Resources, which formulates the 3R strategy, aimed at Reducing, Reusing, and Recycling of waste. An analysis of recently adopted documents, the Plastic Resource Circulation Act of 2021 in particular, demonstrates that special emphasis is placed on 2R: waste reduction and reuse, which is successfully achieved thanks to the high level of environmental awareness of Japanese citizens and thoughtful and multifaceted educational work with the population. Over the past decade, Japan has seen a steady reduction of municipal solid waste. However, while remaining one of the world leaders in the field, it is currently faced with a number of difficulties, such as a low recycling rate and a significant volume of incinerated waste. It is concluded that significant progress in this area is impossible without clearer goal setting for the volume of solid waste processing that would meet modern world standards.